Development of Serious Games as A Programming Learning Platform for Informatics Students - Prasetya, Noven Indra; Syidada, Shofiya; Retnawati, Lestari (Universitas Pendidikan Mandalika, 2025)
This study aims to develop DolananCoding, a programming learning platform based on serious games designed for informatics students. The research employed the waterfall software development methodology, encompassing requirements analysis, system design, implementation, testing, and dissemination. The study participants consisted of second- and fourth-semester students from the Department of Informatics at Universitas Wijaya Kusuma Surabaya, totaling 264 students. The research instrument used is the end-user computing satisfaction (EUCS) questionnaire with a 5-point Likert scale to evaluate user satisfaction with the platform. Data analysis was conducted using descriptive statistics to assess user satisfaction across five dimensions: accuracy, ease of use, content, timeliness and format. The results indicated that the DolananCoding platform was validated and has received positive responses from students, achieving a user satisfaction score of 4.3 out of 5.0. This platform is expected to enhance students' motivation and engagement in programming learning while equipping them with the programming skills required to compete in the professional job market.